2020
DOI: 10.1111/dom.14039
|View full text |Cite
|
Sign up to set email alerts
|

Semaglutide improves health‐related quality of life versus placebo when added to standard of care in patients with type 2 diabetes at high cardiovascular risk (SUSTAIN 6)

Abstract: Aim To assess what drives change in health‐related quality of life (HRQoL) in type 2 diabetes in the SUSTAIN 6 trial and identify potential mediators of the treatment effect of semaglutide on HRQoL scores. Materials and Methods The Short Form (SF)‐36v2® questionnaire [comprising physical component summary (PCS) and mental component summary (MCS)] was used to assess changes in HRQoL from baseline to week 104, by treatment, in a prespecified analysis. This post‐hoc analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 28 publications
2
19
0
Order By: Relevance
“…One of these studies did find that treatment-related improvements in mental health were blunted among those experiencing three or more hypoglycaemic episodes, 29 but the other reported no change in Mental Component scores. 24 Moreover, the latter was consistent with a study examining mental health using a subscale of the RAND Corporation 36-item (RAND-36) survey-a measure that parallels the SF-36-which found no change in mental health following self-treated hypoglycaemia. 22 Taken as a whole, findings from health status studies (n = 9) indicated perceptions of health worsened among those experiencing hypoglycaemic over a period of 6-36 months, but only for events severe enough to require assistance.…”
Section: Health Statussupporting
confidence: 80%
See 1 more Smart Citation
“…One of these studies did find that treatment-related improvements in mental health were blunted among those experiencing three or more hypoglycaemic episodes, 29 but the other reported no change in Mental Component scores. 24 Moreover, the latter was consistent with a study examining mental health using a subscale of the RAND Corporation 36-item (RAND-36) survey-a measure that parallels the SF-36-which found no change in mental health following self-treated hypoglycaemia. 22 Taken as a whole, findings from health status studies (n = 9) indicated perceptions of health worsened among those experiencing hypoglycaemic over a period of 6-36 months, but only for events severe enough to require assistance.…”
Section: Health Statussupporting
confidence: 80%
“…Database searches identified 12,571 records. Abstract and title screening excluded 12,096 records, and full‐text screening eliminated 460 records, leaving 15 studies 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 that satisfied inclusion criteria. Backward and forward citation searches of these studies identified 3 additional studies, 35 , 36 , 37 and hand searches identified 2 studies, 38 , 39 resulting in 20 total studies selected for extraction and synthesis (Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…In our study, the lowest reported SF-36 subscale score was for physical functioning (and vitality), and the highest was for bodily pain. Our mean PCS and MCS values were similar to those reported by clinical trials investigating the cardiovascular and subjective outcomes of new medication [ 52 ].…”
Section: Discussionsupporting
confidence: 85%
“…Additionally, CV benefits and positive effects on some kidney outcomes have been shown with OW semaglutide in participants with T2D 22,23 . Compared with BBI, the lower number of injections required with OW semaglutide may also enhance treatment adherence and QoL 8,24,25 …”
Section: Introductionmentioning
confidence: 99%